Economic Feasibility Study of Integrated Virtual Power Plants with Renewables for Railway System in Germany - Zhakiyev, Nurkhat; Heisig, Philipp; Wolff, Carsten (International Journal of Energy Economics and Policy, 2025)
This study examines whether a traction-oriented virtual power plant can deliver cost-competitive, low-carbon electricity into Deutsche Bahn’s 110 kV/16.7 Hz railway network and defines the contractual and technological conditions for bankability. The considered case study consists of a 104 MW portfolio – 60 MW wind and 40 MW PV as the primary focus, complemented by 2 MW run-of-river and 2 MW biogas that are included as an possible extension of the model – together with 20 MWh of storage, and integrates dedicated 16.7 Hz conversion. To evaluate the economic viability of this portfolio, we apply a model with scenarios varying Power Purchase Agreement (PPA) tenor (10, 20, 30 years), discount rates (2-6%), and tariffs. Results show contract tenor as the key determinant of viability: extending the PPA from 10 to 30 years reduces LCOE from ~7.4 to ~6.1 ct€/kWh and increases NPV roughly threefold. Price for frequency-conversion hardware significantly influences deployment. A transparent marginal-price mechanism for rural prosumers, reflecting temporal and locational value while covering conversion and balancing costs, aligns incentives and enables stable participation without direct subsidies. For practice, railway operators should prioritise 20-30-year PPAs with clear converter-performance and harmonics standards. Regulators can support deployment through standardised 16.7 Hz interconnection rules and modest credit enhancements. Community benefits are maximised via simple, transparent contracts and predictable revenue streams. The study’s originality lies in coupling techno-economic modelling with frequency-specific engineering constraints, delivering quantitative thresholds for bankability and a practical pricing model for community suppliers, addressing gaps in current rail-energy integration research.